Kapasitas Aparat Inspektorat dalam Pengawasan Keuangan Daerah Kabupaten Sidoarjo (Kajian terhadap Kompetensi Aparat Inspektorat di Kabupaten Sidoarjo) - Tuding, Daniel Saleppang (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
Based on experience during for five (5) years (2007-2011), the Inspectorate as the internal supervision of government officials in the regional administration in Sidoarjo, has not been able to play the role optimally as the consultant (consulting), the quality assurance (quality assurance) and provide early warning (early warning system) to prevent or reduce the potential of the irregularities in the financial management area.The results of investigation from the Institution of Finance Audit (IFA) to the Local Government Finance Report (LGFR) of Sidoarjo Regency for 5 (five) years (2007-2011), has indicate that there are materially and significantly things that related to the asset and local financial management. It’s the reason why the government of Sidoarjo regency obtain this opinions ; Unnatural (2007), Fair With Exception (2008), Not Stated Opinion (2009) and Fair With Exception (2010 and 2011). These findings are in the form of the non-compliance with laws and regulations, the fraudulance and the noncompliance with the financial statement presentation.